TaC coating with through-type through hole and application of TaC coating

By depositing a TaC coating with through-type through-holes on a graphite substrate, the problems of obstacles in the atmosphere transmission of raw materials and uneven temperature fields during the growth of silicon carbide single crystal substrate are solved, and high-quality and low-stress silicon carbide crystals are achieved Grow and improve the temperature and corrosion resistance of graphite substrates.

CN119145056APending Publication Date: 2024-12-17SICC CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202310713244.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-06-15
Publication Date
2024-12-17

AI Technical Summary

Technical Problem

During the preparation of silicon carbide single crystal substrate, the existing TaC plating has high density that impedes the atmosphere of raw material, reduces the crystal growth rate, uneven temperature field, and the difference in thermal expansion between SiC crystals and graphite substrates leads to uneven stress, which affects the influence of uneven stress, Crystal mass.

Method used

TaC coating with through-type through-holes is deposited on the surface of graphite substrate, and TaC coating is formed through spraying process, bubbles are introduced to form through holes, which improves the atmosphere transmission rate and temperature field uniformity of raw materials, reduces stress, and controls through sintering. Grain orientation and size enhance binding force with graphite substrate.

Benefits of technology

Improve the growth rate and quality of silicon carbide crystals, reduce internal stress, enhance the temperature resistance and chemical corrosion resistance of graphite substrates, avoid the thermal expansion and extrusion of crystals by graphite substrates in the thermal field, and prolong the TaC coating. The service life of the layer and graphite substrate.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119145056A_ABST
    Figure CN119145056A_ABST
Patent Text Reader

Abstract

The invention discloses a TaC coating with a through-type through hole and application of the TaC coating, and belongs to the technical field of semiconductor preparation. The TaC coating is deposited on the surface of the graphite base material, and the TaC coating contains through type through holes. The TaC coating can improve the temperature resistance and chemical corrosion resistance of the graphite base material, and the through-type through holes contained in the TaC coating can ensure the atmosphere transmission of raw materials in crystal growth and improve the uniformity of a temperature field at the same time, so that the internal stress in the crystal is reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to a TaC coating with through-type through holes and application thereof, belonging to the technical field of semiconductor preparation. Background Art

[0002] The third-generation semiconductor silicon carbide (SiC) single crystal substrate has become the preferred semiconductor material for the preparation of GaN-based high-frequency microwave devices due to its excellent physical properties such as large bandgap, high resistivity and thermal conductivity, and strong breakdown field. With the continuous development of high-power devices such as 5G technology and new energy vehicles, the market demand for silicon carbide single crystal substrates continues to expand. More importantly, mass commercial applications have also put forward higher requirements on the quality of silicon carbide single crystal substrates.

[0003] As a high-melting point, high-strength, corrosion-resistant high-temperature coating material, TaC is widely used in semiconductor, photovoltaic and aerospace fields due to its excellent physical and chemical properties. Generally, TaC coatings are required to be highly dense to ensure that the internal substrate it protects is not corroded. However, since the currently industrialized silicon carbide uses the physical vapor method (PVT) for crystal growth, the high-density TaC coating will hinder the transmission of the atmosphere of the silicon carbide raw material, thereby reducing the crystal growth rate; and the crystal growth temperature in the PVT method is relatively high, accompanied by the flow field changes of the C and Si atmospheres, which reduces the uniformity of the temperature field of crystal growth, thereby affecting the growth quality of the crystal. And because there are differences in thermal expansion coefficient and thermal conductivity between SiC crystals and graphite, when SiC crystals come into contact with graphite at high temperatures, due to the difference in thermodynamic properties, the graphite will expand and squeeze the SiC crystal due to heat, thereby causing defects such as polycrystalline, polymorphic and dislocation in the SiC crystal. Summary of the invention

[0004] In order to solve the above problems, a TaC coating with through-type through holes and its application are provided. The TaC coating is deposited on the surface of a graphite substrate, and can improve the temperature resistance and chemical corrosion resistance of the graphite substrate. The TaC coating contains through-type through holes, which can ensure the transmission of the raw material atmosphere during crystal growth while improving the uniformity of the temperature field, thereby reducing the internal stress in the crystal, and can also avoid the edge stress of the crystal caused by thermal expansion and extrusion of the graphite substrate in the thermal field, thereby improving the uniformity of the crystal stress distribution.

[0005] According to one aspect of the present application, a TaC coating having through-type through holes is provided. The TaC coating is deposited on the surface of the graphite substrate, and the TaC coating contains through-type through holes.

[0006] The TaC coating is uniformly deposited on the surface of the graphite substrate, which can increase the contact area with the graphite substrate, thereby improving the bonding force between the TaC coating and the graphite substrate. The interface bonding strength between the TaC coating and the graphite substrate is 9-15Mpa. The TaC coating contains through-holes, which can improve the transmission rate of the silicon carbide raw material atmosphere while improving the uniformity of the temperature field during crystal growth, thereby increasing the growth rate of the crystal and reducing the internal stress of the crystal, thereby obtaining a high-quality and low-stress silicon carbide crystal.

[0007] Optionally, the aperture of the through-type through hole is 2-7 μm, preferably 2.3-6.1 μm. The aperture of the through-type through hole can not only improve the transmission rate of the silicon carbide raw material atmosphere, but also the diameter of the through hole is in the micron level, which will not reduce the protection performance of the graphite substrate, and when the graphite substrate is heated and expanded, the through-type through hole can avoid the direct contact reaction between the crystal and the graphite, thereby preventing the graphite from reacting with the SiC crystal as a carbon source, causing an imbalance in the C / Si ratio, reducing the lattice distortion of the crystal edge, and avoiding the crystal from being squeezed by the thermal expansion of the graphite substrate in the thermal field to produce edge stress, further reducing the stress in the crystal.

[0008] Optionally, the through-type through holes are evenly distributed in the TaC coating, and the density of the through-type through holes is 160-310 / mm 2 The uniformly distributed through-type through holes are also uniformly distributed on the surface of the graphite substrate, thereby improving the transmission uniformity of the silicon carbide raw material atmosphere and further improving the temperature field uniformity during crystal growth. The density of the through-type through holes can ensure that the TaC coating protects the graphite substrate, improves the corrosion resistance of the graphite substrate, and can reduce the thermal expansion of the graphite substrate, thereby reducing the negative impact of the graphite substrate on the crystal during crystal growth.

[0009] Optionally, the thickness of the TaC coating is 30-400 μm, the TaC grains in the TaC coating are arranged in a stacking staggered manner, and the size of the TaC grains is 15-50 μm. The thickness of the TaC coating can improve the temperature resistance and chemical corrosion resistance of the graphite substrate, and the arrangement of the TaC grains can reduce the stress of the TaC coating. Even if cracks or grain boundaries appear in the TaC coating during the crystal growth process, the cracks can be contained within a short axial distance to avoid the generation of through cracks, thereby improving the protection of the graphite substrate.

[0010] Optionally, the TaC grains in the TaC coating are oriented and grow along the

[200] and

[220] directions. The growth direction of the TaC grains can improve the compactness of the TaC coating, thereby improving the bonding strength between the TaC coating and the graphite substrate, as well as the temperature resistance and thermal chemical corrosion resistance of the TaC coating. The growth direction of the TaC grains combined with the size of the TaC grains can reduce the contact gap between the TaC grains, increase the contact area between adjacent TaC grains, and thus improve the bonding force between the TaC grains.

[0011] Optionally, the method for preparing the TaC coating having through-type through holes comprises the following steps:

[0012] (1) Prepare slurry: 25-40 parts of TaC powder, 5-8 parts of Ta 2 O 5 , 20-35 parts of a solvent, 15-25 parts of a co-solvent, 1-3 parts of an air entraining agent, 2-5 parts of a thickener, 5-15 parts of a straight-chain saturated aliphatic hydrocarbon and 1-3 parts of carbon powder are mixed and stirred to obtain a slurry containing TaC;

[0013] (2) The slurry is sprayed onto the surface of a graphite substrate, the temperature is increased to cause bubble bursting, and then the slurry is dried and sintered to obtain the TaC coating having through-holes.

[0014] The addition of the air entraining agent in step (1) of the present application can introduce uniform bubbles into the slurry containing TaC. The bubbles break to form pores during the drying process of the slurry, and solidify in the TaC coating during the subsequent sintering process to form through-holes from the surface to the graphite substrate, thereby increasing the growth stress and growth rate of the crystal. In step (2), a spraying process is used to form the TaC coating. The spraying process can form multiple crystal nuclei, so that the crystal nuclei of the TaC coating grow in an oriented manner in the

[200] and

[220] directions, and finally form a multi-layer grain layer. Compared with the TaC coating prepared by the existing CVD method, the formation of through cracks can be avoided, thereby increasing the protection of the graphite substrate.

[0015] Optionally, the spraying is electrostatic spraying, which can improve the adhesion and distribution uniformity of the slurry on the surface of the graphite substrate, thereby improving the bonding between the TaC coating and the graphite substrate, and improving the uniformity of the distribution of the through-type through holes on the surface of the graphite substrate. The spraying amount and the number of spraying times of the electrostatic spraying can be selected according to the thickness of the TaC coating to be prepared.

[0016] Optionally, the stirring rate in step (1) is 700-800 r / min, and the stirring time is 2-3 h. The above stirring rate and stirring time can improve the uniformity of the mixing of the raw materials, and help to improve the uniformity of the size and number of bubbles in the slurry, and can also prevent the bubbles from bursting during the stirring process.

[0017] Optionally, in step (2), the temperature of the bubble bursting process is 60-80°C and the time is 2-4h; the drying process is 180-220°C and the drying time is 8-12h. Preferably, the temperature of the bubble bursting process is 70°C and the time is 3h; the drying process is 200°C and the drying time is 10h. The sprayed slurry is treated at 60-80°C for 2-4h to preliminarily dry the TaC coating and slowly burst the bubbles introduced by the air entraining agent. This temperature and time can ensure uniform bubble bursting and avoid cracking or thickness changes of the TaC coating during bubble bursting, thereby improving the uniformity of the TaC coating. The drying process is to allow the solvent in the slurry to evaporate completely, improve the volatilization efficiency of the solvent, and thus save the production time of the TaC coating.

[0018] Optionally, in step (2), the sintering is performed under an inert gas, and the sintering includes:

[0019] Sinter at 700-900 mbar and 500-700°C for 3-5 hours; then increase the pressure to 1000-1100 mbar, the temperature to 1600-1800°C, and sinter for 8-10 hours; then adjust the pressure to 145-155 kPa, increase the temperature to 2200-2400°C, sinter for 14-16 hours, and finally reduce to room temperature and normal pressure within 15-25 hours;

[0020] Preferably, in step (2), the sintering comprises:

[0021] Sintering was carried out at 800 mbar and 600 °C for 4 h; then the pressure was increased to 1000 mbar, the temperature was increased to 1700 °C, and sintering was carried out for 9 h; then the pressure was adjusted to 150 kPa, the temperature was increased to 2300 °C, and sintering was carried out for 15 h, and finally the temperature was reduced to room temperature and normal pressure within 20 h. Sintering at 500-700℃ is the stage of grain nucleation. The pressure of 700-900mbar can increase the nucleation rate and improve the size uniformity of nucleation in combination with temperature. Sintering at 1600-1800℃ is the transition growth stage of grains. The pressure of 1000-1100mbar combined with the sintering temperature can control the growth rate of grains and promote the oriented growth of grains along the

[200] and

[220] directions. 2200-2400℃ is the grain growth stage. Sintering at this temperature for 14-16h is conducive to grain growth. The pressure of 145-155kPa can control the oriented growth direction of grains and the size of final grains, and improve the consistency of grain size and orientation. Reducing to room temperature and normal pressure within 15-25h can release the stress in the TaC coating evenly, improve the quality of the TaC coating, and reduce the probability of cracks in the TaC coating during crystal growth.

[0022] Optionally, the air entraining agent is selected from any one or more of rosin resin, alkyl, alkyl aromatic sulfonic acid, fatty alcohol sulfonate, saponin, protein salt or petroleum sulfonic acid, preferably a saponin air entraining agent. The above-mentioned air entraining agent can introduce bubbles into the slurry and improve the dispersion of bubbles in the slurry, so that the bubbles are uniformly attached to the surface of the graphite substrate during the spraying of the slurry, which is conducive to the subsequent formation of through-type through holes. It has been verified that the saponin air entraining agent has the best dispersion in the slurry, the bubble volume uniformity generated is good, and the size consistency of the through-type through holes can be improved.

[0023] Optionally, the solvent is selected from at least one of ethanol, propanol, n-butanol, acetone and butanone; and the co-solvent is selected from at least one of tetrahydrofuran, chloroform and glycerol.

[0024] Optionally, the porosity of the graphite substrate is 5% to 55%. Since the graphite substrate itself has pores, during slurry spraying, a small portion of the slurry penetrates into the interior of the graphite substrate, further increasing the bonding area between the TaC coating and the graphite substrate and improving the bonding strength between the two.

[0025] Preferably, the slurry comprises, by weight: 32.7 parts TaC powder, 6 parts Ta 2 O 5 , 25 parts of ethanol, 20 parts of tetrahydrofuran, 1.5 parts of saponin-type air entraining agent, 3.5 parts of thickener, 10 parts of straight-chain saturated aliphatic hydrocarbon, and 1.3 parts of carbon powder. TaC powder is used as the solute. 2 O 5 Provide Ta source, carbon powder as flux and carbon source, ethanol as solvent, tetrahydrofuran as co-solvent. In order to enhance the bonding strength between the coating and the graphite base, a certain degree of chemical reaction needs to be introduced in the process. 2 O 5 As a Ta source, graphite is a C source, and the two can react to form TaC.

[0026] Preferably, the thickener is cellulose ether.

[0027] According to another aspect of the present application, there is provided a use of the TaC coating having through-type through holes as described in any one of the above items in the preparation of graphite parts and semiconductor materials.

[0028] The graphite piece is a graphite piece with the TaC coating coated on the surface.

[0029] Preferably, the semiconductor material is silicon carbide material.

[0030] More preferably, the silicon carbide material is conductive silicon carbide or semi-insulating silicon carbide.

[0031] More preferably, the crystal form of the silicon carbide material is one of 2H-SiC, 4H-SiC, 6H-SiC, 3C-SiC, and 15R-SiC.

[0032] The beneficial effects of this application include but are not limited to:

[0033] 1. According to the TaC coating with through-type through holes of the present application, the TaC coating is deposited on the surface of the graphite substrate, which can increase the contact area and bonding force with the graphite substrate, protect the graphite substrate, and improve the temperature resistance and chemical corrosion resistance of the graphite substrate, thereby reducing the interference of the graphite substrate on the crystal growth environment and improving the stability of the crystal environment.

[0034] 2. According to the TaC coating with through-type through holes of the present application, the TaC coating contains through-type through holes, which can ensure the transmission of raw material atmosphere during crystal growth while improving the uniformity of the temperature field, so that it can be used to prepare low-stress silicon carbide crystals.

[0035] 3. According to the TaC coating with through-type through holes of the present application, the air entraining agent can introduce bubbles into the slurry and be evenly attached to the surface of the graphite substrate through a spraying process, thereby improving the distribution uniformity and size uniformity of the through-type through holes. The preparation process is simple, and the oriented growth of grains in the TaC coating can be controlled through calcination and sintering processes, thereby improving the production efficiency of the TaC coating.

[0036] 4. According to the TaC coating with through-type through holes of the present application, the sintering process can control the orientation and size of the TaC grains, and enable a multi-layer grain layer to be formed in the TaC coating. The TaC grains in adjacent grain layers are staggered, thereby avoiding the occurrence of through-cracks in the TaC coating during use and extending the service life of the TaC coating and the graphite substrate. BRIEF DESCRIPTION OF THE DRAWINGS

[0037] The drawings described herein are used to provide a further understanding of the present application and constitute a part of the present application. The illustrative embodiments of the present application and their descriptions are used to explain the present application and do not constitute an improper limitation on the present application. In the drawings:

[0038] Figure 1 This is the morphology characterization diagram of TaC coating 1#.

[0039] Figure 2 This is the XRD test diagram of TaC coating 1# and TaC in Example 1 of the present application. DETAILED DESCRIPTION

[0040] The present application is described in detail below with reference to embodiments, but the present application is not limited to these embodiments.

[0041] Unless otherwise specified, the raw materials in the examples of this application were purchased through commercial channels.

[0042] Example 1

[0043] This embodiment relates to a TaC coating having a through-type through hole, and the preparation method thereof comprises the following steps:

[0044] (1) Preparation of slurry: 32.7 parts of TaC powder, 6 parts of Ta 2 O 5 , 25 parts of ethanol, 20 parts of tetrahydrofuran, 1.5 parts of saponin-type air-entraining agent, 3.5 parts of cellulose ether, 10 parts of straight-chain saturated aliphatic hydrocarbon and 1.3 parts of carbon powder were mixed, and stirred at 700 r / min for 2.5 h to obtain a slurry containing TaC;

[0045] (2) The slurry of step (1) is electrostatically sprayed onto the surface of the graphite substrate, the temperature is raised to 70°C, maintained for 3 hours to burst the bubbles, dried at 200°C for 10 hours, and then sintered: sintered at 800 mbar and 600°C for 4 hours; then the pressure is increased to 1000 mbar, the temperature is increased to 1700°C, and sintered for 9 hours; then the pressure is adjusted to 150 kPa, the temperature is increased to 2300°C, sintered for 15 hours, and finally cooled to room temperature and normal pressure within 20 hours to obtain TaC coating 1#.

[0046] Example 2

[0047] This embodiment relates to a TaC coating having a through-type through hole, and the preparation method thereof comprises the following steps:

[0048] (1) Prepare slurry: 25 parts of TaC powder, 5 parts of Ta 2 O 5 , 20 parts of ethanol, 15 parts of tetrahydrofuran, 1 part of saponin-type air-entraining agent, 2 parts of cellulose ether, 5 parts of straight-chain saturated aliphatic hydrocarbons and 1 part of carbon powder are mixed, and stirred at 800 r / min for 2 hours to obtain a slurry containing TaC;

[0049] (2) The slurry of step (1) is electrostatically sprayed onto the surface of the graphite substrate, the temperature is raised to 60°C, maintained for 4 hours to burst the bubbles, dried at 180°C for 12 hours, and then sintered: sintered at 700 mbar and 500°C for 5 hours; then the pressure is increased to 1000 mbar, the temperature is increased to 1600°C, and sintered for 10 hours; then the pressure is adjusted to 145 kPa, the temperature is increased to 2200°C, and sintered for 16 hours, and finally cooled to room temperature and normal pressure within 15 hours to obtain TaC coating 2#.

[0050] Example 3

[0051] This embodiment relates to a TaC coating having a through-type through hole, and the preparation method thereof comprises the following steps:

[0052] (1) Prepare slurry: 40 parts of TaC powder, 8 parts of Ta 2 O 5 , 35 parts of ethanol, 25 parts of tetrahydrofuran, 3 parts of saponin-type air-entraining agent, 5 parts of cellulose ether, 15 parts of straight-chain saturated aliphatic hydrocarbon and 3 parts of carbon powder were mixed, and stirred at 700 r / min for 3 hours to obtain a slurry containing TaC;

[0053] (2) The slurry of step (1) was electrostatically sprayed onto the surface of the graphite substrate, the temperature was raised to 80°C, maintained for 2 hours to burst the bubbles, dried at 220°C for 8 hours, and then sintered: sintered at 900 mbar and 700°C for 3 hours; then the pressure was raised to 1100 mbar, the temperature was raised to 1800°C, and sintered for 8 hours; then the pressure was adjusted to 155 kPa, the temperature was raised to 2400°C, and sintered for 14 hours, and finally cooled to room temperature and normal pressure within 25 hours to obtain TaC coating 3#.

[0054] Example 4

[0055] The difference between this embodiment and embodiment 1 is that in step (1), the raw materials are mixed and stirred at 700 r / min for 5 min, and the other conditions are the same as those in embodiment 1, to obtain TaC coating 4#.

[0056] Example 5

[0057] The difference between this embodiment and embodiment 1 is that in step (2), the slurry of step (1) is electrostatically sprayed onto the surface of the graphite substrate, the temperature is raised to 200° C., maintained for 13 hours to burst the bubbles and dried, and then sintered. The other conditions are the same as in embodiment 1 to obtain TaC coating 5#.

[0058] Example 6

[0059] The difference between this embodiment and embodiment 1 is that in step (2), the sintering is as follows: sintering at 400 mbar and 400°C for 4 hours; then the pressure is increased to 1000 mbar, the temperature is increased to 1700°C, and sintering is performed for 9 hours; then the pressure is adjusted to 150 kPa, the temperature is increased to 2300°C, and sintering is performed for 15 hours, and finally the temperature is reduced to room temperature and normal pressure within 20 hours. The remaining conditions are the same as those in embodiment 1, and TaC coating 6# is obtained.

[0060] Example 7

[0061] The difference between this embodiment and embodiment 1 is that in step (2), the sintering is as follows: sintering at 800 mbar and 600°C for 4 hours; then the pressure is increased to 1000 mbar, the temperature is increased to 1200°C, and sintering is performed for 9 hours; then the pressure is adjusted to 150 kPa, the temperature is increased to 2300°C, and sintering is performed for 15 hours, and finally the temperature is reduced to room temperature and normal pressure within 20 hours. The remaining conditions are the same as those in embodiment 1, and TaC coating 7# is obtained.

[0062] Example 8

[0063] The difference between this embodiment and embodiment 1 is that in step (2), the sintering is as follows: sintering at 800 mbar and 600°C for 4 hours; then the pressure is increased to 1000 mbar, the temperature is increased to 1700°C, and sintering is performed for 9 hours; then the pressure is adjusted to 120 kPa, the temperature is increased to 2500°C, and sintering is performed for 15 hours, and finally the temperature is reduced to room temperature and normal pressure within 20 hours. The remaining conditions are the same as those in embodiment 1, and TaC coating 8# is obtained.

[0064] Comparative Example 1

[0065] Compared with Example 1, this comparative example adopts the CVD method to prepare the TaC coating, specifically:

[0066] The graphite substrate was placed in a chemical vapor deposition furnace, evacuated to below 50 Pa, and then heated to 1200 ° C. ethane, TaCl 5 , H 2 The mixed gas composed of argon gas and carrier gas is kept at a stable flow rate into the deposition furnace, and the furnace pressure is kept at 5000Pa. 5 The molar ratio of TaCl to ethane gas was controlled at 1.2:1 to form a transition layer with a thickness of 50 μm. 5 The molar ratio of the gas to ethane is 3:1, and a TaC coating with a thickness of 60 μm is formed, namely, a comparative TaC coating D1# is prepared.

[0067] Comparative Example 2

[0068] Compared with Example 1, the raw materials in the slurry of step (1) are different: BYK defoamer is used to replace the saponin air entraining agent, and the other conditions are the same as those in Example 1, that is, a comparative TaC coating D2# is prepared.

[0069] Comparative Example 3

[0070] Compared with Example 1, the raw materials in the slurry of step (1) are different: TaCl 5 Replace Ta 2 O 5 , and the other conditions were the same as those in Example 1, so that a comparative TaC coating D3# was obtained.

[0071] Figure 1 This is the morphology characterization diagram of TaC coating 1#, reference Figure 1 (a) is the microscopic morphology of a TaC coating with through-holes, with holes of similar shape and size evenly distributed on its surface; Figure 1 (b) is the bubble morphology taken during the preparation of the TaC coating, in which it is clearly seen that the bubble size is uniform, so that the TaC coating with through-hole morphology is prepared, and its through-holes are also evenly distributed; Figure 1 (c) The coating is polished until the base graphite is exposed, and holes are still visible at this time, thus proving that the holes formed are through holes; Figure 1 (d) shows the SEM and EDS mapping of the coating demo cross section. The image clearly shows the distribution of TaC and the penetration of the holes, and it is confirmed to be a Ta-containing coating through EDS. Figure 1 (e) is a SiC substrate grown using a TaC coating with through-holes. Raman stress mapping test was performed on it, and it was found that the stress distribution in the surface was uniform and the stress was small. Figure 2 It can be seen that the TaC grains in TaC coating 1# grow along the

[200] and

[220] directions.

[0072] Test Example 1

[0073] The TaC coatings 1#-8# and the comparative TaC coatings D1#-D3# prepared in the above embodiments and comparative examples were subjected to cross-sectional SEM test and EDS spectrum analysis, element composition and proportion analysis were performed by EDS, and element distribution was characterized by EDS Mapping, the thickness of the TaC coating, the average pore size and density of the through-type through holes in the TaC coating, and the size of the TaC grains were tested. The test results are shown in Table 1;

[0074] Table 1

[0075]

[0076] Test Example 2

[0077] The TaC coatings 1#-8# and the comparative TaC coatings D1#-D3# prepared in the above embodiments and comparative examples were subjected to high temperature corrosion and thermochemical corrosion experiments, simulating the growth environment of the third-generation semiconductor SiC crystal using the PVT method, and the TaC coatings 1#-8# and the comparative TaC coatings D1#-D3# were kept at 2300°C and etched in SiC atmosphere for 100 hours. The test results are shown in Table 2:

[0078] Table 2

[0079] sample Weight before experiment (g) Weight after the experiment (g) Erosion weight loss rate (%) TaC coating 1# 753 702 6.8 TaC coating 2# 714 639 10.5 TaC coating 3# 742 701 5.5 TaC coating 4# 747 714 4.4 TaC coating 5# 760 721 5.1 TaC coating 6# 741 708 4.5 TaC coating 7# 755 716 5.2 TaC coating 8# 749 698 6.8 Comparison with TaC coating D1# 797 769 3.5 Comparison with TaC coating D2# 761 707 4.1 Comparison with TaC coating D3# 759 704 6.5

[0080] In Table 2, erosion weight loss rate = [(weight before experiment - weight after experiment) / weight before experiment] × 100%. The above high temperature erosion and thermochemical erosion experiments include the weight loss rates of the graphite substrate and the TaC coating, which proves that the TaC coating of the present application can improve the protection performance of the graphite substrate, extend the tolerance and corrosion resistance of the TaC coating, and thus extend the service life of the graphite substrate.

[0081] Test Example 3

[0082] The graphite substrates of TaC coating 1# and comparative TaC coating D1# were used as crucibles for growing silicon carbide crystals. The same mass of silicon carbide powder was added into the crucibles and the furnace was vacuumed to 10 -6 mbar, and then introduce high-purity inert gas to 300 mbar. Repeat this process 3 times and finally evacuate the furnace to 10 -6 mbar or less; introduce high-purity inert gas into the furnace body, raise the pressure to 40 mbar within 1 hour, and continue to introduce high-purity inert gas to keep the pressure constant; crystal growth stage: while keeping the pressure constant, raise the temperature in the furnace body to 2100K within 5 hours, and the growth time is 5 hours, and raise the temperature in the furnace body to 2350K within 2 hours, and the growth time is 75 hours; after the single crystal growth is completed, open the furnace body, take out the crucible, and obtain silicon carbide single crystal 1# and silicon carbide single crystal D1#.

[0083] Performance tests were carried out on silicon carbide single crystal 1# and silicon carbide single crystal D1#. At any horizontal plane, the radial stress of silicon carbide single crystal 1# was -10~10Mpa, and the difference between the central stress of silicon carbide single crystal 1# and the edge stress of silicon carbide single crystal 1# was no more than 20Mpa; the radial stress of silicon carbide single crystal D1# was -30~40Mpa, and the difference between the central stress of silicon carbide single crystal D1# and the edge stress of silicon carbide single crystal D1# was greater than 20Mpa; in any axial test, the axial stress of silicon carbide single crystal 1# was -10~10Mpa, and the axial stress of silicon carbide single crystal D1# was -25~25Mpa.

[0084] The above is only the embodiment of the present application, and the protection scope of the present application is not limited by these specific embodiments, but is determined by the claims of the present application. For those skilled in the art, the present application can have various changes and variations. Any modification, equivalent replacement, improvement, etc. made within the technical ideas and principles of the present application should be included in the protection scope of the present application.

Claims

1. A TaC coating having a through-hole, characterized in that: The TaC coating is deposited on the surface of the graphite substrate, and the TaC coating contains through-holes.

2. The TaC coating having through-holes according to claim 1, characterized in that: The diameter of the through-hole is 2-7 μm, preferably 2.3-6.1 μm.

3. The TaC coating with through-holes according to claim 1, characterized in that: The through-type through holes are evenly distributed in the TaC coating, and the density of the through-type through holes is 160-310 / mm 2 .

4. The TaC coating with through-holes according to claim 1, characterized in that: The thickness of the TaC coating is 30-400 μm, the TaC grains in the TaC coating are arranged in a stacking staggered manner, and the size of the TaC grains is 15-50 μm.

5. The TaC coating with through-holes according to claim 1, characterized in that: The TaC grains in the TaC coating grow in an orientation manner along the [200] and [220] directions.

6. The TaC coating with through-type through holes according to any one of claims 1 to 5, characterized in that: The preparation method of the TaC coating comprises the following steps: (1) preparing a slurry: 25-40 parts of TaC powder, 5-8 parts of Ta2O5, 20-35 parts of a solvent, 15-25 parts of a co-solvent, 1-3 parts of an air entraining agent, 2-5 parts of a thickener, 5-15 parts of a straight-chain saturated aliphatic hydrocarbon and 1-3 parts of a carbon powder are mixed and stirred to obtain a slurry containing TaC; (2) The slurry is sprayed onto the surface of a graphite substrate, the temperature is increased to cause bubble bursting, and then the slurry is dried and sintered to obtain the TaC coating having through-holes.

7. The TaC coating with through-holes according to claim 6, characterized in that: In step (2), the bubble bursting process is carried out at a temperature of 60-80°C and a time of 2-4 hours; In the drying process, the drying temperature is 180-220° C. and the drying time is 8-12 hours.

8. The TaC coating with through-holes according to claim 6, characterized in that: In step (2), the sintering is performed under an inert gas, and the sintering includes: Sinter for 3-5 hours at 700-900 mbar and 500-700°C; then increase the pressure to 1000-1100 mbar, the temperature to 1600-1800°C, and sinter for 8-10 hours; then adjust the pressure to 145-155 kPa, increase the temperature to 2200-2400°C, sinter for 14-16 hours, and finally reduce to room temperature and normal pressure within 15-25 hours.

9. The TaC coating with through-holes according to claim 6, characterized in that: The air entraining agent is selected from any one or more of rosin resins, alkyls, alkyl aromatic sulfonic acids, fatty alcohol sulfonates, saponins, protein salts or petroleum sulfonic acid, preferably a saponin air entraining agent; and / or The solvent is selected from at least one of ethanol, propanol, n-butanol, acetone and butanone; the co-solvent is selected from at least one of tetrahydrofuran, chloroform and glycerol.

10. Use of the TaC coating with through-type through holes according to any one of claims 1 to 9 in the preparation of graphite parts and semiconductor materials.